Strategi Pemberdayaan Masyarakat Miskin Melalui Pengembangan Kelompok Usaha Bersama (Studi Kasus Pada KUBE Fakir Miskin “Sama Handi’ di Kecamatan Kurun, Kabupaten Gunung Mas) - Siska Karunia; Jhon Wardie; Eka Nor Taufik (Journal of Environment and Management, 2020)
This study aims to describe the general description of KUBE management activities 'Sama Handi' in Kurun District, Gunung Mas Regency. It also intends to formulate a strategy for empowering the poor through the development of KUBE 'Sama Handi'. A SWOT analysis was used to describe qualitatively the data obtained through field observations, interviews/discussions, and documentation. The results suggest that the priority strategies for empowering the poor are: (1) Strategy for increasing livestock population, (2) Strategy for strengthening group institution, (3) Strategy for increasing companion?s capacity building, (4) Strategy for enhancing breeders? capacity, (5) Strategy to convert waste into organic and biogas fertilizers. Further, to support the development of KUBE 'Sama Handi' as an agribusiness centre for cattle barns, some strategies can be applied, namely (1) improving marketing system and animal management; (2) capital strengthening; (3) integrating animal husbandry area; and (4) development of livestock supporting infrastructure.